Travel motivation among cross border tourists: Case study of Langkawi - Park, Jonghyun; Musa, Ghazali; Moghavvemi, Sedigheh; Thirumoorthi, Thinaranjeney; Taha, Azni Zarina; Mohtar, Mozard; Sarker, Md Moniruzzaman (Elsevier, 2019)
Research that focuses on regional tourists in Malaysia is scarce in literature. This study examined the influence of travel motivations; economic, nature, and cultural aspects on tourists’ loyalty intention in the context of Langkawi Island, Malaysia. A total of 200 fully answered questionnaires were collected from ASEAN tourists on the island using the purposive sampling technique, and the data were analyzed using the structural equation modeling technique. The results confirmed that the ‘economic aspect’ and ‘nature aspect’ are important motivational factors affecting tourists’ loyalty intention to revisit Langkawi. Although cultural aspect influences loyalty intention, its effect was weak. Managerial and marketing recommendations were made for tourism in Langkawi based on these findings. © 2019 Elsevier Ltd